Probable electrokinetic phenomena in tropical peat: a review - Asadi, Afshin; Moayedi, Hossein; Kim Huat, Bujang; Parsaie, Alireza (Academic Journals, 2011)
Peat is unconsolidated superficial deposits with high non-crystalline colloid (humus) content, constituting the subsurface of wetland systems. Electrokinetic techniques are innovative ground improvement methods for soft soils. Peats have noticeable qualities to make a suitable environment for utilization of electrokinetic techniques, i.e. (i) the saturated mass is a good environment, (ii) the high charge and high specific surface area of the humus increases the presence of cations for a water momentum in an electro-osmotic phenomenon, (iii) the surface charge may cause electro-osmosis to occur, (iv) the decomposition processes affect the electro-osmotic behavior, (v) the resistivity may affect the electro-osmotic behavior. Introducing cations as a bridge between clay and humus surfaces may stabilize the peat from a geotechnical view point. The expectations of this review have to be proven by conducting some electro-osmotic experiments.